APA Handbook of Testing and Assessment in Psychology, Vol. 1: Test Theory and Testing and Assessment in Industrial and Organiza 2013
DOI: 10.1037/14047-031
|View full text |Cite
|
Sign up to set email alerts
|

Holistic assessment for selection and placement.

Abstract: Max Simoneit was the chief of German military psychology during World War II. The Germans believed that victory depended on the superior leadership and intellect of the officer (Ansbacher, 1941). Simoneit, therefore, believed that psychological diagnosis (i.e., character analysis) of officer candidates and specialists should be the primary focus of Copyright American Psychological Association. Not for further distribution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…The inferiority of intuitive decision making compared with statistical models in selection processes has been previously demonstrated (Ægisdóttir et al, 2006; Dawes, 1971; Dawes et al, 1989; Ganzach et al, 2000; Grove, Zald, Lebow, Snitz, & Nelson, 2000; Highhouse & Kostek, 2013). The present study extended the generality of this pattern to situations that involve an attribute that affects the selection process but is irrelevant to the position.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The inferiority of intuitive decision making compared with statistical models in selection processes has been previously demonstrated (Ægisdóttir et al, 2006; Dawes, 1971; Dawes et al, 1989; Ganzach et al, 2000; Grove, Zald, Lebow, Snitz, & Nelson, 2000; Highhouse & Kostek, 2013). The present study extended the generality of this pattern to situations that involve an attribute that affects the selection process but is irrelevant to the position.…”
Section: Discussionmentioning
confidence: 97%
“…There is robust support for the inferiority of intuitive predictions. For example, when future success of undergraduate students is predicted on the basis of information from various sources (e.g., GRE and grade point average), previous studies have shown that intuitive judgments are less accurate than statistically based ones (Alexakos, 1966; Dawes, 1971; Hess & Brown, 1977; Highhouse & Kostek, 2013).…”
mentioning
confidence: 99%
“…This body of research strongly supports the use of standardized data collection methods, like structured interviews, that uniformly Personnel Assessment And decisions Attributions And EmployEE sElEction gather information about candidates (McDaniel, Whetzel, Schmidt, & Mauer, 1994;Schmidt & Hunter, 1998) and standardized data combination techniques, like mathematical formulae, that integrate information analytically to create overall applicant evaluations (Borman, 1982;Highhouse & Kostek, 2010;Tziner & Dolan, 1982;Wollowick & McNamara, 1969). Practitioners, nevertheless, continue to prefer unstructured and intuition-based approaches to hiring that compromise the reliability and predictive validity of employee selection systems by exposing the hiring process to the idiosyncratic beliefs and biases of decision makers (Arthur et al, 2006;Conway et al, 1995;Ryan et al, 1999;Simola et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Nonstandardized employee selection practices, like unstructured interviews and intuitive combination, typically provide practitioners with considerable control over the decision-making process. Practitioners are able determine which attributes to evaluate, how the attributes are evaluated, and the relative importance of attribute information (Dipboye, 1994;Highhouse & Kostek, 2010;Huffcutt & Arthur, 1994). Conversely, standardized employee selection practices are specifically designed to limit the influence practitioners have over the decision-making process (Gatewood et al, 2010;Meehl, 1954).…”
Section: Personnel Assessment and Decisionsmentioning
confidence: 99%
“…Research strongly supports the use of standardized assessment methods, like structured interviews, to evaluate applicants (Highhouse & Kostek, 2010; McDaniel, Whetzel, Schmidt, & Maurer, 1994; Schmidt & Hunter, 1998). Many practitioners, 1 however, continue to prefer unstructured and intuition-based approaches to hiring (Boatman & Erker, 2012; Ryan, McFarland, & Shl, 1999; Simola, Taggar, & Smith, 2007; van der Zee, Bakker, & Bakker, 2002).…”
mentioning
confidence: 94%